Evans-Kishimoto type argument for actions of discrete amenable groups on McDuff factors - Masuda, Toshihiko (Mathematica Scandinavica, 2007)
We apply the Evans-Kishimoto type argument to centrally free actions of discrete amenable groups on McDuff factors, and classify them. Especially, we present a different proof that the Connes-Takesaki modules are complete cocycle conjugacy invariants for centrally free actions of discrete amenable groups on injective factors.